Just Like a Barrette that Claws, that Clasps, that Clips, that Cunts: metonymy, metaphor, and simile in Angela Carr’s The Rose Concordance - Markotić, Nicole (Studies in Canadian Literature, 2013)
Playing on the many meanings and linguistic roles of the word "like," Nicole Markotić responds to Angela Carr’s poetry book, The Rose Concordance, which "translates" lines in the keyword index to the thirteenth-century poem Roman de la rose. Referencing canonical poems about love by William Blake, Robert Burns, Christopher Marlowe, and Gertrude Stein, Markotić moves through a discussion of contemporary poets that include Carla Harryman, Phil Hall, Susan Holbrook, and Nikki Reimer. In The Rose Concordance, Carr takes on the patriarchy of the traditional poetic address and questions the role of the female figure within such structures, the way that the body does or does not run from lyric complicity. The Rose Concordance, like Roman de la rose, proffers rose as metonymic for lover. Carr uncovers the layers of previous manuscripts that propose coupled love in a particularly pronoun-gendering way. As part of that uncovering, the concordance becomes a museum, a fine archive, a compendium, and a catalogue. In her work, Carr addresses an archival love that severs itself from lyric tradition at the very moment that it excavates itself from and burrows into that tradition.